2021
DOI: 10.3389/feduc.2020.587266
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Schoolteachers' Attitudes and Perceptions Regarding Inclusive Education Implementation: The Interaction Effect of Help-Seeking Preference and Collegial Climate

Abstract: While the special needs education system in Japan has shifted from a segregated approach to a more inclusive one, the actual implementation of this approach may be less than ideal. The implementation of inclusive education faces several challenges, such as difficulty in meeting individual needs and lack of medical support systems in general school settings. With this in mind, we conducted a web-based survey of Japanese schoolteachers to empirically examine their attitudes and perceptions regarding inclusive ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…What is needed now is to promote a correct understanding of disability and make people aware of the potential value of the "Help Mark." Especially for the Japanese society, which is considered to have difficulties in realizing an inclusive society (11), it is important to simultaneously increase the correct understanding of people with disabilities and awareness of the "Help Mark," and this study proposes one concrete method to do so. However, this study has some limitations.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is needed now is to promote a correct understanding of disability and make people aware of the potential value of the "Help Mark." Especially for the Japanese society, which is considered to have difficulties in realizing an inclusive society (11), it is important to simultaneously increase the correct understanding of people with disabilities and awareness of the "Help Mark," and this study proposes one concrete method to do so. However, this study has some limitations.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Suppose the possibility of such prejudice and labeling makes people with disabilities hesitant to utilize the “Help Mark,” and, as a result, the “Help Mark” is not well known to the public. In that case, this will go against the original purpose of the “Help Mark.” What is needed now is to promote a correct understanding of disability and make people aware of the potential value of the “Help Mark.” Especially for the Japanese society, which is considered to have difficulties in realizing an inclusive society ( 11 ), it is important to simultaneously increase the correct understanding of people with disabilities and awareness of the “Help Mark,” and this study proposes one concrete method to do so.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…This experiment was conducted over two weeks. Before manipulation (week 1), according to the procedures as in previous studies [ 3 ], participants were asked to read brief descriptions regarding segregated and inclusive education (see Additional file 1 ) and indicate their evaluations of agreeableness and benefit regarding the two, using a 7-point Likert scale (from 1 “strongly disagree” to 7 “strongly agree”). A week later, they were asked to participate in the experiment again (week 2).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that the Japanese people somewhat (university students, general samples, people with disabilities, and schoolteachers) approved of and agreed on the idea of inclusive education. However, they also underestimated its feasibility [ 3 , 5 ]. Blindly promoting and introducing inclusive education in Japan, with lower perceptions of its feasibility particularly among schoolteachers, may have undesirable consequences, such as not only less assumed benefits from inclusive education for the children with disabilities, but also producing confusion in the field of education.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we surmised that creating a collegial organizational climate might play an important role in countering the association between a low level of help-seeking and mental health problems. A collegial climate or the concept of collegiality among schoolteachers can be defined as a relationship in which schoolteachers can share information and exchange their opinions to develop a common understanding, and support and enhance each other in the environment for school education without qualms, regardless of their age or position ( Maeda and Hashimoto, 2020 ; Maeda et al, 2021 ). This organizational collegial climate in schools has also been a focus in educational and school psychology in the Japanese cultural context.…”
Section: Introductionmentioning
confidence: 99%